Aplikasi berbagai jenis pemberian konsentrasi asam amino sitokinin dan giberelin pada tanaman melon (Cucumis melo L.) hidroponik - Tri Rini Kusparwanti; Rindha Rentina Darah Pertami; Eliyatiningsih Eliyatiningsih; Edi Siswadi; Abdurrahman Salim Salim (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: This study aims to determine the growth and yield of melon plants in drip irrigation systems in conventional and hydroponic cultivation techniques. Method: The research was carried out in July – September 2022, on the Smart GreenHouse area of ​​the Jember State Polytechnic with an altitude of ± 89 meters above sea level and an air temperature of 22 – 32 °C. Parameters observed were plant height (cm), plant diameter (cm), number of leaves (strands), fruit weight per sample (kg), fruit brix content per sample (0brix), fruit diameter per sample (cm). Result: Based on the results the t-test recapitulation of the use of drip irrigation systems in conventional and hydroponic melon cultivation gave a significant effect on the observation of plant height at 2 – 6 WAP, plant diameter at 2 WAP and 3 WAP, number of leaves at 2 – 6 WAP, as well as giving effect on yield parameters, namely fruit weight, fruit brix content, and melon fruit diameter. Conclusion: The conclusion of this study is that the use of drip irrigation systems in conventional and hydroponic melon cultivation has a significant effect on all plant parameters. However, it did not affect the parameters of plant diameter at the age of 4 - 6 WAP. The use of this drip irrigation system is well applied to the cultivation of melon plants with substrate hydroponic cultivation techniques using coco peat growing media.